2005
DOI: 10.1143/jjap.44.2147
|View full text |Cite
|
Sign up to set email alerts
|

Re-Examination of Impact of Intrinsic Dopant Fluctuations on Static RAM (SRAM) Static Noise Margin

Abstract: The impacts of intrinsic threshold voltage (V th) fluctuations in metal oxide semiconductor field effect transistors (MOSFETs) on the static random access memory (SRAM) static noise margin (SNM) are re-examined in the 90 nm to 45 nm technology generations on the basis of the 2003 International Technology Roadmap for Semiconductors (ITRS). The V th fluctuations due to random dopant fluctuations are calculated using the cube model and the deviations in SNM are derived using tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 7 publications
0
30
0
Order By: Relevance
“…In particular, the stability of SRAM cells is largely affected by random V th variability of cell transistors [2][3][4]. Recently, a new concept of a post-fabrication selfimprovement technique of SRAM cell stability by simply applying high voltage to V DD terminal has been proposed and demonstrated [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the stability of SRAM cells is largely affected by random V th variability of cell transistors [2][3][4]. Recently, a new concept of a post-fabrication selfimprovement technique of SRAM cell stability by simply applying high voltage to V DD terminal has been proposed and demonstrated [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most significant barriers for further supply voltage (V DD ) scaling in SRAM is the random variability of transistors [1][2][3][4][5][6]. The minimum operation voltage (Vmin) in large scale SRAM cell array is much higher than that in logic circuits [7], which obstructs low voltage operation of SRAM and forces very complicated circuit design.…”
Section: Introductionmentioning
confidence: 99%
“…The stability of SRAM cells is usually characterized by static noise margin (SNM) [1][2][3][4][5][6]. However, since the stability of SRAM array is determined by the worst cell in the cell array, it is hard to quantitatively compare the cell stability by merely SNM in different technologies.…”
Section: Introductionmentioning
confidence: 99%
“…DIBL variability has a great impact on the circuit performance and static random-access memory (SRAM) stability. 19,20) It has been already reported that DIBL is mainly decided by channel potential profile along the gate length due to RDF. 21) In order to design reliable logic circuits and SRAM, the precise statistical modeling of COV and DIBL variability is essential.…”
Section: Introductionmentioning
confidence: 99%